Manutenção da prática de atividade física e indicadores hemodinâmicos, metabólicos e inflamatório em adultos: análise transversal e coorte de 12 meses - Lima, Manoel Carlos Spiguel [UNESP] (2014)
Aim: (i) to compare blood flow and mediointimal thickness indicators between active and sedentary adults throughout life, as well as, (ii) to analyze the relationship between these variables (adjusted by lipid profile, inflammatory indicator and behavioral variables) after a follow-up of 12 months. Methods: A cross-sectional and a cohort study of 12 months were carried out with at least 96 individuals of both sexes. All of the potential participants selected were put in to the experiment or apply in the established inclusion criteria: (i) persistently active (active in childhood, adolescence and currently physically active in leisure) or persistently sedentary (inactive in childhood, adolescence and currently sedentary in leisure), (ii) age between 30 and 50 years old, (iii) no previous history of brain stroke or heart attack, (iv) no amputation or visual problem due to diabetes mellitus. The sample was subdivided in two groups (persistently active, persistently inactive), which were paired by sex, ethnic and age (30-39 years / 40-50 years). Initially, the experiment was composed by three questionnaires (an anamnesis [history of illness, medication use, dietary habits, smoking and alcohol habits], sleep quality and current physical activity in leisure, work and locomotion). All participants have been measured: (i) anthropometry (body weight, height and waist circumference), (ii) estimation of body composition (dual-energy X-ray absorptiometry), (iii) pedometer (used for the period of seven days, which was fixed in waist high and only removed during sleep and shower), (iv) blood pressure, rest heart rate and heart rate variability, (v) blood sample for biochemistry analysis (triglycerides, total cholesterol, high density lipoprotein, low density lipoprotein, very low density lipoprotein, glucose, insulin and C-reactive protein ultrasensitive) and (vi) image exam of ultrasonography with Doppler of common carotid and femoral arteries to obtain..